The Influence Of Liquidity, Solvency, And Profitability On The Financial Performance Of Food And Beverage Manufacturing Companies Listed On The Indonesia Stock Exchange For The 2021-2024 Period - Jhanita Fransisca; Angelika Subur; Wiliam Wiliam; Hendra Saputra; Nasib Nasib (Jurnal Economic Resource, 2026)
This study aims to examine the impact of liquidity, solvency, and profitability on the financial performance of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange (IDX) for the years 2021–2024. The study employs a quantitative explanatory methodology utilizing secondary data derived from audited financial statements. Researchers utilized a purposive sampling strategy to choose 16 organizations as research samples. The examination of the data included classical assumption tests, multiple linear regression, partial t-tests, simultaneous F-tests, and the coefficient of determination. The findings indicate that liquidity (Current Ratio), solvency (Debt to Equity Ratio), and profitability (Return on Assets) each exert a positive and significant influence on financial performance as assessed by Return on Equity. At the same time, the three independent variables have a big effect on financial performance, with a good correlation (R = 0.828). This means that 68.6% of the changes in ROE can be described by CR, DER, and ROA, while the other 31.4% is due to other factors that are not part of the model. These results show how important it is for businesses to keep their capital structure healthy, manage their liquidity at the right level, and make more money in order to increase shareholder value and keep their business going